(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Recurring violations of ethical practices in the workplace are negative phenomena that significantly impact public trust in the financial sector, reflecting adversely on economic stability at both national and global levels. In this context, participants in financial markets are increasingly aware of and comprehend the importance of sectors committed to sustainability, ethical investment, and green finance. Moreover, this understanding extends to systems that mitigate the harmful effects of capitalist behavior. In this context, corporate commitment to social responsibility entails preparing reports and financial statements characterized by transparency and credibility, indicating a low level of profit management practices by the management of these companies. The current research aims to explore the relationship between profit management practices and social responsibility, focusing on determining whether social responsibility serves as a regulatory tool restricting profit management practices. The study highlights the importance of companies dedicating sufficient attention to their social responsibilities, given their direct impact on business outcomes, alongside the urgent need to raise awareness of the positive aspects of profit management practices.